1997
DOI: 10.1016/s0092-8674(00)80516-4
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Receptor Coactivator ACTR Is a Novel Histone Acetyltransferase and Forms a Multimeric Activation Complex with P/CAF and CBP/p300

Abstract: We report here the identification of a novel cofactor, ACTR, that directly binds nuclear receptors and stimulates their transcriptional activities in a hormone-dependent fashion. ACTR also recruits two other nuclear factors, CBP and P/CAF, and thus plays a central role in creating a multisubunit coactivator complex. In addition, and unexpectedly, we show that purified ACTR is a potent histone acetyltransferase and appears to define a distinct evolutionary branch to this recently described family. Thus, hormona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
1,026
1
9

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,377 publications
(1,060 citation statements)
references
References 55 publications
24
1,026
1
9
Order By: Relevance
“…Note in this respect that PLZF was shown to speci®cally bind the N-Cor and SMRT co-repressors (Dhordain et al, 1997;Hong et al, 1997). These proteins recruit histone deacetylase complexes and could induce irreversible changes in the chromatin state (Chen et al, 1997b;Nagy et al, 1997;Grignani et al, 1998;Guidez et al, 1998;Lin et al, 1998). The third explanation is an implication of the reciprocal RARa/PLZF product, whose mRNA is found in all t(11;17) patients.…”
Section: Discussionmentioning
confidence: 98%
“…Note in this respect that PLZF was shown to speci®cally bind the N-Cor and SMRT co-repressors (Dhordain et al, 1997;Hong et al, 1997). These proteins recruit histone deacetylase complexes and could induce irreversible changes in the chromatin state (Chen et al, 1997b;Nagy et al, 1997;Grignani et al, 1998;Guidez et al, 1998;Lin et al, 1998). The third explanation is an implication of the reciprocal RARa/PLZF product, whose mRNA is found in all t(11;17) patients.…”
Section: Discussionmentioning
confidence: 98%
“…A recent clinical study using 560 human breast tumor tissues found the AIB1 expression along with expression of genes involved in cell migration and invasion such as polyomavirus enhancer activator 3 and matrix metalloproteinases 2 and 9 suggesting a positive correlation of AIB1 expression with tumor metastasis [95]. The AIB1 coactivator activates ERα-dependent transcription by recruiting HAT such as p300 and P/CAF to ERα target gene chromatin [175]. AIB1 interacts with ERα in a ligand-dependent fashion and its coactivator activity is potentiated by CK1δ and PKCε-mediated phosphorylation of AIB1 in breast cancer cells [176,177].…”
Section: Estrogen Receptor Coregulators In Breast Cancer Coactivatorsmentioning
confidence: 99%
“…Transcriptional squelching between members of the nuclear receptor family suggested the existence of intermediary cofactors. A number of nuclear receptor interacting proteins have been characterized that speci®cally bind to the hormone-binding domain of the receptor in the presence of ligand, some of them, including histone acetyltransferases like CBP and its homolog p300, P/ CAF and ACTR were shown to behave unequivocally as true co-activators (Chen et al (1997) and references therein). Conversely, in the absence of ligand, RARs (and their related thyroid hormone receptors TRs) behave as transcriptional repressors.…”
Section: Introductionmentioning
confidence: 99%